2014
DOI: 10.1155/2014/240760
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soy Bean Flour Enriched Bread Intake on Anthropometric Indices and Blood Pressure in Type 2 Diabetic Women: A Crossover Randomized Controlled Clinical Trial

Abstract: Previous studies showed that soy bean has the potential to improve many aspects of diabetes state and provide metabolic benefits that aid in weight management. We aimed to determine the effects of soy bean flour enriched bread on anthropometric indices and blood pressure among type 2 diabetic patients. This randomized, crossover, clinical trial was performed in 30 type 2 diabetic women. There were two trial periods for 6 weeks and a wash-out period for 4 weeks. In the soy bread diet period, 120 g of soy bean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Dietary fiber stimulates the secretion of gastrointestinal hormones that may act as satiety factors. 22 At the baseline, the levels of plasma lipids were similar between the two groups. In male subjects who completed the trial, the levels of TC, LDL-C, triglyceride and non HDL-C increased in both the groups.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Dietary fiber stimulates the secretion of gastrointestinal hormones that may act as satiety factors. 22 At the baseline, the levels of plasma lipids were similar between the two groups. In male subjects who completed the trial, the levels of TC, LDL-C, triglyceride and non HDL-C increased in both the groups.…”
Section: Discussionmentioning
confidence: 82%
“…In male subjects who completed the trial, the levels of TC, LDL-C, triglyceride and non HDL-C increased in both the groups. The studies by Salari Moghaddam et al 22 and St-Onge et al 30 also reported that the groups consuming bread reinforced with soybean powder or foods with added soy protein did not significantly change serum lipid profiles compared with the group taking the placebo. Many clinical studies have obtained conflicting results on the effects of soy, fermented soybean and isoflavones on lipid metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[48] Moreover, 30 premenopausal women were given soybean flour fortified bread as a dietary intervention (120 g for 6 weeks) prepared by replacing 30% of wheat flour with soybean flour to see the protective effect of soy intake on the development of diabetes but no significant effect on metabolic profile was observed. [49] Isoflavones and Cancer…”
Section: Potential Health Benefits Of Soy Isoflavonesmentioning
confidence: 99%